New Directions in the Ethics of Assisted Suicide and Euthanasia - Cholbi, Michael; Varelius, Jukka (Cham Springer International Publishing, 2023)
This book provides novel perspectives on ethical justifiability of assisted dying in the revised edition of New Directions in the Ethics of Assisted Suicide and Euthanasia. Going significantly beyond traditional debates about the value of human life, the ethical significance of individual autonomy, the compatibility of assisted dying with the ethical obligations of medical professionals, and questions surrounding intention and causation, this book promises to shift the terrain of the ethical debates about assisted dying. The novel themes discussed in the revised edition include the role of markets, disability, gender, artificial intelligence, medical futility, race, and transhumanism. Ideal for advanced courses in bioethics and healthcare ethics, the book illustrates how social and technological developments will shape debates about assisted dying in the years to come
Chapter 1. Assisted Dying and the Proper Role of Patient Autonomy (Emma C. Bullock) -- Chapter 2. Preventing Assistance to Die: Assessing Indirect Paternalism Regarding Voluntary Active Euthanasia and Assisted Suicide (Thomas Schramme) -- Chapter 3. Autonomy, Interests, Justice and Active Medical Euthanasia (Julian Savulescu) -- Chapter 4. Mental Illness, Lack of Autonomy, and Physician-Assisted Death (Jukka Varelius) -- Chapter 5. Assisted Dying for Individuals with Dementia: Challenges for Translating Ethical Positions into Law (Jocelyn Downie) -- Chapter 6. Clinical Ethics Consultation and Physician Assisted Suicide (David M. Adams) -- Chapter 7. License to Kill: A New Model for Excusing Medically Assisted Dying? (Richard Huxtable) -- Chapter 8. Saving Lives with Assisted Suicide and Euthanasia: Organ Donation After Assisted Dying (David M. Shaw) -- Chapter 9. Everyday Attitudes About Euthanasia and the Slippery Slope Argument (Adam Feltz) -- Chapter 10. “You Got Me Into This...”: Procreative Responsibility and Its Implications for Suicide and Euthanasia (Rivka Weinberg) -- Chapter 11. Due Care in the Context of Euthanasia Requests by Persons with Psychiatric Illness: Lessons from a Recent Criminal Trial in Belgium (Marc De Hert) -- Chapter 12. Medical Futility and Assisted Dying (Nancy S. Jecker) -- Chapter 13. Medical Aid in Dying: The Case of Disability (Christopher A. Riddle) -- Chapter 14. A Feminist Approach to Medical Aid in Dying: Identifying a Path Forward (Jennifer A. Parks) -- Chapter 15. Envisioning Markets in Assisted Dying (Michael Cholbi) -- Chapter 16. Robots, AI, and Assisted Dying: Ethical and Philosophical Considerations (Ryan Tonkens) -- Chapter 17. Dying to Live: Transhumanism, Cryonics, and Euthanasia (Adam Buben) -- Chapter 18. When is Self-perceived Burden an Acceptable Reason to Hasten Death? (Michael Gill)
Keywords: Bioethics; Philosophy of Medicine; Medicine / Philosophy